PERAN KOMITMEN ORGANISASI DALAM MEMEEDIASI PENGARUH PROGRAM PELATIHAN, PENGEMBANGAN KARIR DAN PENILAIAN KINERJA TERHADAP INTENTION TO STAY - Setyadi, Taufik; Budiyono, Rokhmad (Sekolah Tinggi Ilmu Ekonomi Semarang, 2021)
The research problem raised in this study is to analyze the effect of training programs, career development and performance appraisals on intention to stay with organizational commitment as an intervening variable.The population in this study were all employees at PT. Life Insurance Generali Indonesia IV Semarang, totaling 48 officers. The sampling technique is a census, which uses the entire population as the research sample. The analysis tool uses multiple linear regression using two stages.The results of this study prove empirically that training programs, career development, and performance appraisals have a positive and significant effect on organizational commitment. Training programs, career development, performance appraisals, and organizational commitment have a significant positive effect on Intention to stay.